2013
DOI: 10.2478/s11686-013-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of cryptic species of Ceratomyxa Thélohan, 1892 (Myxosporea: Bivalvulida) including the description of eight novel species from apogonid fishes (Perciformes: Apogonidae) from Australian waters

Abstract: Ceratomyxa parasites from the gall bladders of 23 species of cardinalfishes (family Apogonidae) from Australian waters were examined for their taxonomic identity and phylogenetic relatedness. We identified 15 of the 23 apogonid fish species infected with species of Ceratomyxa. Although the majority of apogonid species harboured only a single Ceratomyxa species, four were found with multiple species of Ceratomyxa. This study describes eight novel species using a combination of morphological, small subunit ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…The description of this new ceratomyxid reinforces the assumption that species richness of Ceratomyxa in South European sparids is high and that a single sparid host species can be infected by more than one species of Ceratomyxa [11,43], with or without the occurrence of co-infection. On the other hand, molecular systematics have shown that most marine Ceratomyxa are restricted to a single host [15,44,46], so reports based on morphology alone of several species of this genus from multiple hosts suggest that a significant number of known species are yet to be described. For instance, Ceratomyxa diplodae was originally described from Diplodus annularis [35] and later from Dicentrarchus labrax [34] and D. puntazzo [33], but no molecular data were provided in any of these reports.…”
Section: Discussionmentioning
confidence: 99%
“…The description of this new ceratomyxid reinforces the assumption that species richness of Ceratomyxa in South European sparids is high and that a single sparid host species can be infected by more than one species of Ceratomyxa [11,43], with or without the occurrence of co-infection. On the other hand, molecular systematics have shown that most marine Ceratomyxa are restricted to a single host [15,44,46], so reports based on morphology alone of several species of this genus from multiple hosts suggest that a significant number of known species are yet to be described. For instance, Ceratomyxa diplodae was originally described from Diplodus annularis [35] and later from Dicentrarchus labrax [34] and D. puntazzo [33], but no molecular data were provided in any of these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Over 280 Ceratomyxa species have so far been described in fish (Heiniger and Adlard ), of them nine species were described from members of the family Serranidae. None, however, have previously been described from the orange‐spotted grouper E. coioides .…”
Section: Discussionmentioning
confidence: 99%
“… from Plectorhynchus gaterinus (Haemulidae) in the Red Sea; C. buri Yokoyama and Fukuda from cultured yellowtail Seriola quinqueradiata (Carangidae) in Japan; Ceratomyxa flexa Meglitsch from Plagiogenion rubiginosus (Emmelichthyidae) in the Pacific Ocean; Ceratomyxa gibba Meglitsch from Congiopodus leucopaecilis (Congiopodidae) in the Pacific Ocean; Ceratomyxa honckenii Reed et al. from Amblyrhynchotes honckenii (Tetraodontidae) in South Africa; Ceratomyxa ireneae Heiniger and Aldlard, from Archamia fucata (Apogonidae) in the Great Barrier Reef in Australia; Ceratomyxa recta Meglitsch from Genypterus blacodes (Ophidiidae) in the Pacific Ocean in New Zealand; Ceratomyxa sparusaurati SitjÀ‐Bobadilla et al. from Sparus aurata (Sparidae) in the Mediterranean Sea, and Ceratomyxa vepallida Meglitsch from Caulopsetta scapha (Bothidae) in the Pacific Ocean in New Zealand (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…; Whipps ). Phylogenetic analyses of the SSU rRNA gene, therefore, suggest that spore morphology should not be used in isolation for the characterization of new genus or species, but should be associated with phylogenetic analyses (Eszterbauer ; Gunter and Adlard ; Heiniger and Adlard ; Holzer et al. ; Whipps and Kent ).…”
mentioning
confidence: 99%
“…Recently, however, the use of molecular tools to investigate the systematics of myxozoan parasites, mainly based on the SSU rRNA sequence, has revealed many cases of disparity between the molecular taxonomy and that based on morphometric and ecobiological information (Fiala 2006;Fiala and Bartosova 2010;Kent et al 2001;Whipps 2004). Phylogenetic analyses of the SSU rRNA gene, therefore, suggest that spore morphology should not be used in isolation for the characterization of new genus or species, but should be associated with phylogenetic analyses (Eszterbauer 2004;Heiniger and Adlard 2013;Holzer et al 2004;Whipps and Kent 2006). After DNA sequencing, therefore, many studies have shown that some morphologically different myxosporean species that had previously been included in different genera are in fact closely related, while some species with very similar spore morphologies are in fact quite distant from each other genetically (Bartosova and Fiala 2011;).…”
mentioning
confidence: 99%